Vitamin D Effects on Selected Anti-Inflammatory and Pro-Inflammatory Markers of Obesity-Related Chronic Inflammation - Krajewska, Maria; Witkowska-Sędek, Ewelina; Rumińska, Małgorzata; Stelmaszczyk-Emmel, Anna; Sobol, Maria; Majcher, Anna; Pyrżak, Beata (Frontiers in Endocrinology, 2022)
Background: Obesity is related to changes in adipokine secretion, activity of adipose tissue macrophages, helper T cells and regulatory T cells. It has been confirmed that vitamin D has potent anti-inflammatory properties. It contributes to reduction in pro-inflammatory mediators and increase in anti-inflammatory cytokines. There is also evidence that vitamin D could decrease C-reactive protein (CRP) and affect selected haematological indices. Aim of the study: We aimed to evaluate the effect of vitamin D on interleukin (IL)-10, IL-17, CRP, blood leukocyte profile and platelet (PLT) count in overweight and obese children before and after six months of vitamin D supplementation. Material and methods: The study group consisted of 67 overweight and obese children aged 9.08-17.5 years. The control group included 31 normal weight peers age- and sex-matched. None of the studied children had received vitamin D supplementation before the study. Data were analysed at baseline and after vitamin D supplementation. Results: The study group had lower baseline 25(OH)D (p<0.001) and higher white blood cell (WBC) (p=0.014), granulocyte (p=0.015), monocyte (p=0.009) and CRP (p=0.002) compared to the control group. In the study group vitamin D levels were related negatively to nutritional status. Leukocyte profile parameters, PLT, CRP, IL-10 or IL-17 were not related to baseline 25(OH)D. Baseline IL-17 levels correlated with monocytes (R= 0.36, p=0.003) independently on 25(OH)D deficit. In children with vitamin D <15ng/ml, baseline 25(OH)D was related to CRP (R=-0.42, p=0.017). After six months of vitamin D supplementation we noticed decrease in CRP levels (p=0.0003). Serum 25(OH)D correlated with IL-10 in that period (R=0.27, p=0.028). Moreover we noticed that IL-10 correlated with monocyte (R=-0.28, p=0.023). We did not find any significant associations between 25(OH)D and leukocyte profile parameters, PLT or IL-17. The multivariable stepwise regression analysis identified IL-10 as the parameter positively associated with 25(OH)D. Conclusions: Our study confirmed beneficial effects of vitamin D supplementation in overweight and obese paediatric population. Vitamin D intake seems to exert its anti-inflammatory effect mainly via decreasing of CRP level and protecting stabile values of IL-10, rather than its impact on pro-inflammatory factors such as lL-17 and leukocyte profile parameters.